Cultural Translation: Two Modes - Conway, Kyle (TTR, 2013)
This article examines why scholars who theorize cultural translation have not always agreed on what their object of study is. It provides a diachronic account of two competing definitions, one from anthropology and one from cultural studies. It also describes three factors that have complicated debates about cultural translation: the different epistemological and methodological assumptions made by anthropologists and cultural studies scholars; the ambiguous, politically charged relationships linking language, culture, and text; an asymmetry of usage. This article concludes by considering the implications of a point of convergence—the ethical turn taken in anthropology and cultural studies in the last two decades—for debates about attempts to ban Muslim veils from public spaces in North America.